The life and ministry of Jesus. - Taylor, Vincent, 1887-1968. (1955)
"The Jesus of History and the Christ of Faith -- as found in the Gospel records."
Prolegomena -- The period before the Galilean ministry -- The Galilean ministry -- The withdrawal from Galilee -- The Jerusalem ministry -- The passion and resurrection.
A revision and enlargement of the author's The life and ministry of Jesus, published in 1951 in the Interpreter's Bible, v. 7.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Biography; Biographies